Methodological aspects concerning sampling and determination of total selenium and selenium species in geothermal waters - Rusiniak, Piotr; Ruszczyńska, Anna; Wątor, Katarzyna; Bulska, Ewa; Kmiecik, Ewa (Bulletin of Geography. Physical Geography Series, 2020)
The work presents the results of geothermal water sample analysis with respect to the determination of total selenium concentration. For this purpose, geothermal water (GT) samples were collected from three different intakes (GT-1, GT-2, GT-3) with similar temperatures of about 85ºC. Tests were carried out to see if the methodology of sample preparation influenced total selenium concentration during analysis by inductively coupled plasma mass spectrometry (ICP-MS). Samples (raw and filtered) were preserved with nitric acid (HNO3) and mineralised in the laboratory. From the data obtained it was found that there is no significant difference between total selenium concentration in raw and filtered samples. Following mineralisation, the concentrations in the samples were below the limit of detection or limit of quantification. While different analytical steps or procedures are applied, the results of total selenium concentration can vary. Furthermore, high-performance liquid chromatography coupled with ICP-MS was used for the identification of selenium species. The results revealed that hexavalent selenium – Se(VI) – in the geothermal water was found only in samples collected from the GT-2 and GT-3 intakes.